Geographical Association of Bird Species Richness with All-Cause and Cause-Specific Mortality Rates of Local Residents: An Ecological Study in China - Ning Zhang; Jinling You; Qiaochu Xu; Jiacheng Cai; Kelvin P. Jordan; Li Li; Tanchun Yu; Ying Chen (Life)
The pressing ecological challenges of the twenty-first century underscore the need for biodiversity protection. The “One Health” approach, which integrates human, animal, and environmental health, has become increasingly vital. This study investigates the relationship between bird species richness, an important indicator of biodiversity, and both all-cause and cause-specific mortality rates in China. This nationwide county-level ecological study combined citizen science bird data from the China Bird Report Center, all-cause and cause-specific mortality rates of 2021 from the National Mortality Surveillance System, and county-level statistics of population characteristics, socio-economics, education, and healthcare services. We employed univariate and multivariate linear regressions to explore the association between bird diversity and mortality rates. Overall, data from 421 counties revealed a negative association between bird species richness and all-cause mortality rates, with a regression coefficient (95% confidence interval) of −0.197 (−0.376, −0.017). This study also found significant negative associations between bird species richness and cause-specific mortality rates for several diseases, such as cardiovascular diseases (including cerebrovascular and ischemic heart diseases) and cancers (including lung cancer). The effects of associations were similar between both genders. Our findings underscore the significance of biodiversity conservation for public health and highlight the importance of integrated environmental and health policies.